Important moments in the training of Khoja Ahmed Yassaui works - Aлжaнбaевa, У. (Journal of Oriental Studies, 2018)
This article discusses the problems of studying the Sufi religious terms and in the writings of Khoja Ahmed Iassavi and etymology of some words borrowed from Arabic.